Toxicity analysis of gold nanoparticle formulations used for intraocular applications - Amir Reza Hajrasouliha; Ben McCall; Yong Gao; Sunland Lee Gong; Kelsey Robinson; Afshin Izadian (Scientific Reports)
Abstract Gold nanoparticles (AuNPs) possess unique properties for various biological and intraocular applications. In retina research, AuNPs hold promise for therapeutic intervention, drug delivery, and photoreceptor replacement, but their potential toxicity is an area of concern. This study assesses the toxicity of AuNPs formulations suitable for photoreceptor replacement in retinal cells and tissue. Three different gold formulations were studied. One in the form of a single gold nanoparticle with citrate groups (AuNP), an AuNP coated with linkers and superhydrophobic layers (NC), and the NCs mounted on a BaTiO3 nanocore with a high dielectric constant (BTNC). Proliferation assays (PA) and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assays with different concentrations of AuNPs, NC, and BTNC were conducted on human retinal endothelial cell (hREC) cultures. Following intravitreal injection (IVI) of nanoparticles in wild type (WT) mice, function was evaluated with electroretinography (ERG), structural changes through optical coherence tomography (OCT), and vascular change with Isolectin B4 (IB4) postmortem staining. No significant cell death or decreased growth were observed at concentrations below 100ppm in vitro (p-value > 0.05). Mice were examined before and after IVI with nanoparticles, and no major changes were seen. These findings indicate that AuNPs can cause a transient change in the electrophysiology of normal tissue and may impose structural changes at higher concentrations.